Synthesis and Characterization of cds/sio2 Core/shell Nanoparticles Doped with Silver - Kaur, Manveen (My University, 2009)
CdS is a II-VI, direct band gap semiconductor having interesting optoelectronic properties such as photocatalytic and nonlinear optical properties. CdS/SiO2 core/shell nanoparticles have improved applications due to the surface modification of CdS nanoparticles. The mesoporous silica shell of the nanocomposites also plays a key role in the process of fluorescence enhancement, which helps to protect the surface characteristics of QDs, prevent the flocculation of the particles. CdS/SiO2 core/shell nanoparticles doped with silver have been synthesized via the sol-gel technique using hydrolysis of tetraethyl orthosilicate (TEOS). Based on the method, five samples with different concentrations of AgNO3 have been synthesized. The crystal structure and the average crystallite size of the samples have been calculated using X-ray diffraction studies. The elemental analysis has been carried out by EDAX spectroscopy and FTIR spectroscopy. The band gap of CdS/SiO2 core/shell nanoparticles has been calculated by UV-Visible absorption spectra. Room temperature PL studies have been carried out to study the emission characteristics of the synthesized nanoparticles.
M.Sc.(Physics)
Keywords: Cds/ SiO2; Core/ Shell Nanoparticles